Peningkatan Efisiensi Pengolahan Hasil Kopi dan Tebu Melalui Pemanfaatan Pembangkit Listrik Tenaga Surya (PLTS) di Nagari Lasi Kabupaten Agam: Utilizing an Off-Grid Solar Power System to Enhance Coffee Processing Efficiency in Nagari Lasi, Agam Regency - Darwison Darwison; Zaini Zaini; Silvia Permata Sari; Firman Ridwan; Andi Pawawoi; Fauzan Wafi; Dilla Wediya; Irsyad Alghi Fary; Defriyan Hidayat; Fadhila Amanda; Reivan Arya Witama (LPPM Universitas Andalas, 2026)
This program was undertaken to improve the efficiency and sustainability of post-harvest coffee and sugarcane processing in Nagari Lasi, Agam Regency, Indonesia, through the implementation of an off-grid solar photovoltaic (PV) system. Following the eruption of Mount Marapi, local farmers experienced a significant decline in productivity due to their dependence on diesel-powered machinery and limited access to reliable energy sources. To address these challenges, a 540 Wp off-grid solar PV system was installed to provide a clean, renewable, and sustainable power supply for coffee pulping and sugarcane milling. A participatory community development approach was adopted, actively engaging members of the Lasi Reborn Farmers Group throughout the project. The activities included a needs assessment, system design, procurement and installation of solar panels, brushless direct current (BLDC) motors, and maximum power point tracking (MPPT) controllers, followed by laboratory testing, field demonstrations, and operational training. The results demonstrated that the solar PV system performed effectively, achieving an energy conversion efficiency of 87%, reducing fuel-related operating costs by up to 94.4%, and decreasing coffee processing time by approximately 25%, while simultaneously minimizing environmental pollution. Furthermore, capacity-building activities and hands-on training significantly improved farmers' technical competencies and enhanced their energy self-sufficiency. Overall, the project demonstrates that renewable energy-based technologies can improve agricultural productivity, strengthen rural livelihoods, and support sustainable post-disaster recovery in farming communities. These findings highlight the potential of decentralized renewable energy systems as a practical and scalable solution for promoting resilient and sustainable rural development.